2018
DOI: 10.1007/s00405-018-4875-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain effect of preventative shoulder rehabilitation for patients who underwent total laryngectomy with neck dissection

Abstract: In this study, preventative exercise program initiated immediately after surgery had a limited impact on both shoulder function and perceived quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Eighteen ADL/IADL studies (31%) reported non-significant findings with interventions including resistance training, aerobic exercise, toileting behavior and biofeedback, pelvic floor exercises, patient education, swallowing rehabilitation, dietary instruction and training, manual therapy and upper extremity exercise. [150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167] .…”
Section: Activities Of Daily Living and Instrumental Activities Of Daily Living (Adl/iadl)mentioning
confidence: 99%
“…Eighteen ADL/IADL studies (31%) reported non-significant findings with interventions including resistance training, aerobic exercise, toileting behavior and biofeedback, pelvic floor exercises, patient education, swallowing rehabilitation, dietary instruction and training, manual therapy and upper extremity exercise. [150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167] .…”
Section: Activities Of Daily Living and Instrumental Activities Of Daily Living (Adl/iadl)mentioning
confidence: 99%
“…However, given that it was underpowered, without randomisation and with a high risk of bias, it was not felt to provide strong enough evidence to prove equipoise. 15…”
Section: Discussionmentioning
confidence: 99%
“…However, given that it was underpowered, without randomisation and with a high risk of bias, it was not felt to provide strong enough evidence to prove equipoise. 15 Importantly, none of the papers described any adverse effects of therapy. Furthermore, the majority of patients enrolled completed the studies.…”
Section: Summary and Comparisonmentioning
confidence: 99%
“…76 Restorative neck/shoulder exercise interventions were tested in seven studies. 74,75,[77][78][79][80][81][82] Of these, four RCTs with five articles were good quality. Three RCTs examined progressive shoulder strengthening compared with ROM with nonprogressive strengthening exercises in patients with spinal accessory nerve palsy.…”
Section: And Body Composition (4)mentioning
confidence: 98%
“…Eight studies with nine articles investigated the impact of neck/shoulder exercise on neck/shoulder function in HNC patients (total n = 362 patients, median = 42.5, range = 20-76). [74][75][76][77][78][79][80][81][82] Interventions commonly targeted shoulder strengthening (7 studies) and ROM (5), and only one study included neck-focused intervention. 75 Accordingly, the most common primary outcomes involved measures of shoulder disability (5 studies) and ROM (6).…”
Section: And Body Composition (4)mentioning
confidence: 99%